Early frost resistance and permeability properties of carbon fiber/cement-based composite cured by ohmic heating under ultra-low temperature. (3rd May 2021) - Tian, Weichen; Qi, Beimeng; Liu, Yushi; Liu, Keqi; Wang, Wei
Highlights: OH curing method has been utilized to precure CF-CC samples under severely low temperature. Percolation analysis is performed to experimentally and numerically determine optimal CFs content. OH precuring CF-CC shows favorable strength development pre and post freezing action. Water absorption and CO2 diffusion characterizations give prominence to impermeability of OH precuring CF-CC. Mathematical models have been established to predict moisture distribution and carbonation depth of CF-CC. Abstract: Ohmic heating (OH) curing is presented to precure carbon fiber/cement-based composite (CF-CC) under ultra-low temperature to rapidly achieve frost-resisting critical strength. Heat curing temperature is created by ohmic heating effect on CFs conductive network designed by numerical and experimental electric percolation. Frost resistance results show OH precuring can improve the development and recovery of mechanical properties of CF-CC samples comparing with RT precuring pre and post freezing process. Moreover, permeability resistance results demonstrate that OH precuring CF-CC samples possess lower sorptivity and carbonization depth, and the negative effect of extended freezing duration on permeability properties is compensated by OH precuring. Furthermore, the prediction models of moisture distribution and carbonation depth of OH precuring CF-CC samples are established to enhance the evaluation of permeability properties. This work lights up the superiority and application potential of OH curing used as a novel precuring method for cement concrete winter construction at cold region.